2020
DOI: 10.3390/s20236737
|View full text |Cite
|
Sign up to set email alerts
|

Foot Strike Angle Prediction and Pattern Classification Using LoadsolTM Wearable Sensors: A Comparison of Machine Learning Techniques

Abstract: The foot strike pattern performed during running is an important variable for runners, performance practitioners, and industry specialists. Versatile, wearable sensors may provide foot strike information while encouraging the collection of diverse information during ecological running. The purpose of the current study was to predict foot strike angle and classify foot strike pattern from LoadsolTM wearable pressure insoles using three machine learning techniques (multiple linear regression―MR, conditional infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 48 publications
2
7
0
Order By: Relevance
“…The experimental results revealed that the FS patterns were accurately recognized, similar to those reported previously [44]. Contrary to previous studies [44,45], that used pressure-measuring wearable insoles, another recent study utilized an accelerometer inside a running shoe to recognize two different landing styles (e.g., RF and FF strikes) while running [46]. The study found that a cross-correlation measure between acceleration signals from different axes could be used as a feature to recognize the foot strike patterns and the study envisioned the use of acceleration signals for foot strike classification while running.…”
Section: Sensor-based Recognition Of Foot Strike Patternssupporting
confidence: 87%
See 3 more Smart Citations
“…The experimental results revealed that the FS patterns were accurately recognized, similar to those reported previously [44]. Contrary to previous studies [44,45], that used pressure-measuring wearable insoles, another recent study utilized an accelerometer inside a running shoe to recognize two different landing styles (e.g., RF and FF strikes) while running [46]. The study found that a cross-correlation measure between acceleration signals from different axes could be used as a feature to recognize the foot strike patterns and the study envisioned the use of acceleration signals for foot strike classification while running.…”
Section: Sensor-based Recognition Of Foot Strike Patternssupporting
confidence: 87%
“…Similarly, another recent work proposed a foot-striking recognition system based on a pressure-measuring sensor mounted inside a running shoe [45]. The experimental results revealed that the FS patterns were accurately recognized, similar to those reported previously [44]. Contrary to previous studies [44,45], that used pressure-measuring wearable insoles, another recent study utilized an accelerometer inside a running shoe to recognize two different landing styles (e.g., RF and FF strikes) while running [46].…”
Section: Sensor-based Recognition Of Foot Strike Patternssupporting
confidence: 82%
See 2 more Smart Citations
“…Thanks to the fundamentals related to information theory, the miniaturisation of sensors and the improvement of data storage and transmission systems have been possible and is one of the reasons for the success of monitoring and pattern detection through IoT devices and sensors, particularly in the integration of fabrics and textiles (“smart fabrics/wearable”) [ 27 , 28 , 29 , 30 ]. Particularly, the data retrieved by sensors can be used to monitor the elderly in real time and predict their behaviour, preventing potential health problems, while providing them with independence and facilitating them urban living.…”
Section: Introductionmentioning
confidence: 99%